2016
DOI: 10.1089/ten.teb.2015.0453
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Imaging Techniques for Spatiotemporal Characterization of Composition, Microstructure, and Mechanical Properties in Tissue Engineering

Abstract: Ultrasound techniques are increasingly being used to quantitatively characterize both native and engineered tissues. This review provides an overview and selected examples of the main techniques used in these applications. Grayscale imaging has been used to characterize extracellular matrix deposition, and quantitative ultrasound imaging based on the integrated backscatter coefficient has been applied to estimating cell concentrations and matrix morphology in tissue engineering. Spectral analysis has been empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 71 publications
(91 reference statements)
0
34
0
Order By: Relevance
“…The present trends also showed that they may have unique utility in the study of mechanobiology and have high potential to impact the field of tissue engineering as they are further developed and their range of applications expands. The applications and future prospective of ultrasound techniques in the field of tissue engineering was reviewed by Deng CX …”
Section: Mechanical Properties Of Gradient Stiffness Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present trends also showed that they may have unique utility in the study of mechanobiology and have high potential to impact the field of tissue engineering as they are further developed and their range of applications expands. The applications and future prospective of ultrasound techniques in the field of tissue engineering was reviewed by Deng CX …”
Section: Mechanical Properties Of Gradient Stiffness Hydrogelsmentioning
confidence: 99%
“…The applications and future prospective of ultrasound techniques in the field of tissue engineering was reviewed by Deng CX. 94 Puncture testing and elastocapillary bending. Puncture testing is usually used to evaluate hydrogel mechanical failure properties, and it has a key role in their performanceparticularly in load-bearing applications.…”
Section: Mechanical Property Test Of Gradient Stiffness Hydrogelsmentioning
confidence: 99%
“…Several studies have previously shown a relationship between tissue echogenicity and collagen concentration, including for native tissues such as the intestines (Kimmey, et al, 1989), and engineered tissues (Deng, et al, 2016, Mercado, et al, 2015. To the best of our knowledge, ours is the first study to utilize QUS methods to assess the physical properties of nerve fascicles.…”
Section: Discussionmentioning
confidence: 91%
“…Likewise, analyses of ECM can identify global and local matrix physical properties directly affecting cellular behavior and tissue/organ development. For example, ultrasound and atomic force microscopy provide details about ECM architecture, deposition, and function [23–25]. Local stiffening of the ECM with collagen fiber alignment is associated with solid tumors [25–27].…”
Section: Matrix Scaffolding For Cell-matrix Adhesion and Mechanical Smentioning
confidence: 99%